2010
DOI: 10.1177/1934578x1000500532
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of Essential Oils of Genista ulicina and G. vepres

Abstract: The hydrodistilled oils from the aerial parts of Genista ulicina Spach. and G. vepres Pomel., which are endemic to Algeria, were analyzed by gas chromatography-mass spectrometry (GC-MS). In the oil of G. ulicina, 41 compounds were identified representing 90.8% of the total oil, and in G. vepres, 61 compounds representing 84.5% of the total oil. The analyses showed that the major constituents of the oils were lauric acid (14.3%-8.5%), myristic acid (11.5%-5%), linoleic acid (3.1%-11.7%) and palmitic acid (18.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Many researches showed that volatile compounds obtained from many plants are responsible for their pharmacological activities just as non-volatile compounds in herbs (Lograda et al, 2010;Ho et al, 2010;Wei et al, 2012;Sharma et al, 2012;Rahimi et al, 2011). Both EP and FLL contain rich volatile compounds, from which we could always smell the strong fragrance.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches showed that volatile compounds obtained from many plants are responsible for their pharmacological activities just as non-volatile compounds in herbs (Lograda et al, 2010;Ho et al, 2010;Wei et al, 2012;Sharma et al, 2012;Rahimi et al, 2011). Both EP and FLL contain rich volatile compounds, from which we could always smell the strong fragrance.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Genista (Fabaceae family) includes about 90 species of shrubs or small trees in the Mediterranean area and in Western Asia, of which 23 grow in Algeria [1]. This genus is known as a good source of active secondary metabolites like essential oils [2][3][4], saponins [5], quinolizidine alkaloids [6], and flavonoids [7]. A wide range of biological and pharmacological properties has been reported for this genus, such as antimicrobial [8], antioxidant [9], and antiproliferative activities [10].…”
mentioning
confidence: 99%